Effects of trifluralin on nodulation and nitrogen uptake by soybean - Rosolem, Ciro Antonio; Nakagawa, João; Marcondes, Daniel A.S. (Pesquisa Agropecuaria Brasileira, 2014)
The effects of trifluralin upon soybean (Glycine max (L.) Merrill, cv. Paraná) nodulation and nitrogen uptake were studied in two soils, a ’Terra Roxa Estruturada" (clay) and a Dark-Red Latosol (loamy sand), in pots. Doses of 0, 1,2,3 or 4 1/ha of trifluralin were incorporated 8cm deep in the pots, and the soybean plants were harvested at 30, 60 and 90 days after seedling emergence, an nodulation and nitrogen uptake were evaluated. The results allowed for the conclusion that at the earlier stages of soybean growth, in the soil layer with trifluralin there was no nodule development. In the treated pots nodule formation ocurred deeper than in untreated pots. There was not evidence of a direct effect of trifluralin upon nitrogen uptake.